High-resolution repertoire analysis reveals a major bystander activation of Tfh and Tfr cells - Ritvo, Paul-Gydeon (Proc Natl Acad Sci U S A, 2018)
T follicular helper (Tfh) and regulatory (Tfr) cells are terminally differentiated cells found in germinal centers (GCs), specialized secondary lymphoid organ structures dedicated to antibody production. As such, follicular T (Tfol) cells are supposed to be specific for immunizing antigens, which has been reported for Tfh cells but is debated for Tfr cells. Here, we used high-throughput T cell receptor (TCR) sequencing to analyze the repertoires of Tfh and Tfr cells, at homeostasis and after immunization with self- or foreign antigens. We observed that, whatever the conditions, Tfh and Tfr cell repertoires are less diverse than those of effector T cells and Treg cells of the same tissues; surprisingly, these repertoires still represent thousands of different sequences, even after immunization with a single antigen that induces a 10-fold increase in Tfol cell numbers. Thorough analysis of the sharing and network of TCR sequences revealed that a specific response to the immunizing antigen can only, but hardly, be detected in Tfh cells immunized with a foreign antigen and Tfr cells immunized with a self-antigen. These antigen-specific responses are obscured by a global stimulation of Tfh and Tfr cells that appears to be antigen-independent. Altogether, our results suggest a major bystander Tfol cell activation during the immune response in the GCs.